REMEDIASI TANAH TERCEMAR KOBALT (Co) MENGGUNAKAN BIOREMEDIATOR DAN AMELIORAN - Wahyu Purbalisa; Triyani Dewi (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2019)
Soil contains many elements, both macro, micro and metal. Metal elements are generally non-essential. Cobalt (Co) is one of the metallic elements but required in very small amounts for life. At high concentrations of cobalt can cause poisoning. One way to reduce high levels of cobalt in the soil by performing bioremediation plus ameliorant materials. This study consists of two stages. The first stage is the pot scale research with factorial design. The first factor is the bioremediator dose, namely : B0 : Without bioremediator (control), B1 : Bioremediator 20 kg ha-1, B2 : Bioremediator 50 kg ha-1 and the second factor is the application of ameliorant materials, namely: A0 : No ameliorant (control), A1: Biochar + compost (1: 5), A2 : Biochar + compost (2: 5), A3 : Activated charcoal + compost (1 : 5), A4 : Activated charcoal + compost (2 : 5). The second stage is the four best results from the first stage applied in situ on the lysimeter. The results showed that the treatment of bioremediator with a dose of 20 kg ha-1 and activated charcoal + compost (w: w = 2: 5) was able to reduce Co levels in the soil by 76%. The lowest Co level in rice that is equal to 3.06 mg kg-1 was obtained from the treatment of 50 kg bioremediator ha-1 plus active charcoal + compost ameliorant (1: 5).Â